Kajian Normatif terhadap Efektivitas Peraturan Perlindungan Anak dalam Penanggulangan Eksploitasi Anak di Dunia Maya - Nyawiji, Kholifah; Fera; Solihah, Devi Zakiyatus (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The rapid advancement of digital technology has posed significant challenges, particularly concerning the protection of children from online exploitation. This study examines the effectiveness of child protection regulations in Indonesia, addressing the critical issues of increasing cases of child exploitation in cyberspace. The research aims to evaluate the regulatory framework's strengths and limitations while providing actionable recommendations to enhance the system's efficiency. A normative approach was employed, incorporating content analysis of relevant legal documents, comparative law analysis with international regulations, and secondary data from government reports and scholarly literature. The study revealed a consistent increase in reported cases of child exploitation, with limited progress in resolving these cases. Despite existing regulations, systemic issues such as low digital literacy, weak inter-agency coordination, and inadequate resources significantly hinder their implementation. Additionally, Indonesia lags behind developed nations in adopting modern technologies, such as artificial intelligence, for early detection of online exploitation. The findings emphasize the urgent need for strategic investments in digital literacy programs, enhanced law enforcement capabilities, and integration of advanced technologies into child protection mechanisms. Furthermore, this study highlights the critical role of international collaboration in addressing cross-border exploitation. The implications of this research extend to policymakers, legal practitioners, and technology developers, offering a comprehensive perspective on strengthening child protection in the digital age. This research contributes to the theoretical discourse on legal protection and offers practical solutions for developing more robust child protection policies in Indonesia and beyond. Future studies are encouraged to explore longitudinal impacts and the effectiveness of international partnerships in mitigating online child exploitation